Evaluasi Implementasi Mitigasi Kebencanaan di Daya Tarik Wisata Pantai SAMIGITA, Bali (Jurnal Destinasi Pariwisata, 2025)
The implementation of disaster mitigation in tourism destinations is essential to ensure the safety of both tourists and local communities, while supporting the sustainability of the tourism industry. This study aims to evaluate the effectiveness of disaster mitigation implementation at SAMIGITA Beach, Bali, by assessing existing infrastructure, community preparedness, and relevant mitigation policies. A mixed-methods approach was employed, involving qualitative and quantitative techniques, including field observations, in-depth interviews with key stakeholders (BPBD, Balawista, tourism managers, and local communities), and document analysis of existing policies. Primary and secondary data were analyzed using triangulation techniques to ensure the validity of the findings. Results show that the current mitigation infrastructure at SAMIGITA Beach is still inadequate, particularly regarding early warning systems and evacuation routes. The standard operating procedures (SOPs) in place are not yet comprehensive in addressing various disaster threats. The main obstacles include limited budget allocation, poor inter-agency coordination, and low stakeholder engagement. The study recommends the enhancement of early warning technologies, integrated institutional coordination frameworks, and strengthened community-based education programs on disaster mitigation. These strategies are expected to increase disaster preparedness and ensure the long-term sustainability of Kuta, Legian, and Double-Six Seminyak Beaches as resilient and safe tourism destinations.